2021
DOI: 10.5584/jiomics.v11i1.197
|View full text |Cite
|
Sign up to set email alerts
|

Combining detection and reconstruction of correlational and periodic motifs in viral genomic sequences with transitional genome mapping: Application to COVID-19

Abstract: A method of Transitional Automorphic Mapping of the Genome on Itself (TAMGI) is aimed at combining detection and reconstruction of correlational and quasi-periodic motifs in the viral genomic RNA/DNA sequences. The motifs reconstructed by TAMGI are robust with respect to indels and point mutations and can be tried as putative therapeutic targets. We developed and tested the relevant theory and statistical criteria for TAMGI applications. The applications of TAMGI are illustrated by the study of motifs in the g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…where α ϕ is the frequency of nucleotides of the type α retained under reshuffling (the detailed theory for TAMGI, including the derivation of Eq. ( 5), can be found in the paper by Chechetkin & Lobzin (2021)).…”
Section: Correlational Motifs and Transitional Genome Mappingmentioning
confidence: 94%
“…where α ϕ is the frequency of nucleotides of the type α retained under reshuffling (the detailed theory for TAMGI, including the derivation of Eq. ( 5), can be found in the paper by Chechetkin & Lobzin (2021)).…”
Section: Correlational Motifs and Transitional Genome Mappingmentioning
confidence: 94%
“…In particular, coarse-graining of various profiles (e.g., AT/GC content, expression profiles, protein binding profiles) results in a set of stretches within which the characteristics exceed some thresholds. Previously, it was shown that the coarse-grained profiles obtained by transitional automorphic mapping of the genome on itself (TAMGI) contain important information about functional regions in viral genomes [ 55 , 56 ]. The colocalization between stretch sets obtained by coarse-graining of profiles can also be treated by the method developed in our paper.…”
Section: Discussionmentioning
confidence: 99%